QOLP-09. IMPACT OF GLIOBLASTOMA (GBM) PATIENTS' CLINICAL AND TREATMENT CHARACTERISTICS ON CAREGIVER BURDEN AND QUALITY OF LIFE (QOL). (11th November 2019) - Au, Trang; Willis, Connor; Peters, Katherine; Colman, Howard; Cohen, Adam; Leia Nghiemphu, P; Taylor, Jennie; Reblin, Maija; Ryan Ormond, D; Willmarth, Nicole; Menon, Jyothi; Ma, Junjie; et al.
Abstract: BACKGROUND: GBM is an aggressive cancer with poor prognosis. We explored impact of disease on caregivers by characterizing caregiver burden and QOL associated with patient characteristics. METHODS: Primary caregivers of living adult GBM patients with cognitive dysfunction completed a GBM-specific caregiver burden survey and the validated Caregiver Quality of Life Index–Cancer Scale (CQOLC). Patient data were abstracted from medical records (7/2018-4/2019). Patient characteristics were compared between highest and lowest tertile of CQOLC scores (range 0–140); higher scores suggest better QOL. RESULTS: There were 140 patient-caregiver dyads enrolled in the study. Mean patient age was 57 years (range 24–63); majority white males (62.9%), unifocal lesion (90%) and normal activity level at diagnosis. Forty-percent had methylated MGMT promoter status. Caregivers were mostly white (61.4%), college-educated female spouses of similar age; 87.8% were caregiving for >6 months. Median CQOLC score was 82 (tertiles: < 76 and >92). More caregivers in the lowest vs highest CQOLC tertile reported 'not employed due to caregiving' (52.4% vs 12%, P< 0.01), 'changes in patients' personality' (73.3% vs 42.6%, P< 0.01), 'patient memory problems' (93.5% vs 77.1%, P=0.02), and caring for patient with recurrence treated with 'chemotherapy other than temozolomide' ([TMZ], 27.7% vs 8.3%, P=0.01). There was > 10% difference in proportion of caregivers in the lowest vs highest CQOLC tertile for the following patient characteristics: largest lesion in right temporal lobe at baseline and partial resection at initial treatment. Conversely, there was > 10% difference in the highest vs lowest CQOLC tertile for Karnofsky score (> 80), largest lesion in right frontal lobe at baseline, surgical clean margins, TMZ for initial treatment, and surgery for recurrence. CONCLUSION: Unemployment, patient personality/memory changes, and chemotherapy other than TMZ use had significant impact on caregiver burden/QoL. This may help identify caregivers to receive support and intervention.